2009
DOI: 10.1007/s11104-009-0058-2
|View full text |Cite|
|
Sign up to set email alerts
|

Seed P-enrichment as an effective P supply to wheat

Abstract: Most fertilizer phosphorus (P) is sorbed by soil rather than being taken up by crops. We hypothesize enriching wheat seed with P before sowing the crop will reduce requirement of fertilizer P for subsequent wheat production. We produced Penriched wheat (Triticum aestivum L.) seed by soaking the seed in different concentrations of potassium phosphate solution. We found that 0.35 M potassium phosphate was the most effective concentration for P-enrichment of the seed. In pot and field experiments we found that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…, 2009; Burns et al. , 2010; Sekiya & Yano, 2010). But is it feasible to decrease grain P while increasing yield?…”
Section: Allocation Of P To Reproductive Structuresmentioning
confidence: 99%
“…, 2009; Burns et al. , 2010; Sekiya & Yano, 2010). But is it feasible to decrease grain P while increasing yield?…”
Section: Allocation Of P To Reproductive Structuresmentioning
confidence: 99%
“…Increased P bioavailability was studied by inoculation of P-solubilizing bacteria (Canbolat et al 2006;Mishra et al 2008) and P seed coating (Peltonen-Sainio et al 2006;Sekiya & Yano 2010). Burns et al (1988) suggested the use of a stable phosphatase seed coating as a tool to enhance P bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…Plants take up inorganic phosphate (Pi) from soil solution which is usually less than 1µM. This Low inorganic phosphate is due to fixation of P (10.5-15.5 Tg annum -1 ) with aluminum, calcium and iron (Sekiya et al, 2009). This huge accumulation occurs mainly in agricultural soils mostly due to irrational application of P fertilization (Bennett et al, 2001;Carpenter, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This huge accumulation occurs mainly in agricultural soils mostly due to irrational application of P fertilization (Bennett et al, 2001;Carpenter, 2005). One way to increase the P availability and reduce its accumulation is seed priming which may reduce the need for fertilizer P in subsequent crop growth (Sekiya et al, 2009). The higher contents of phosphorous in the seeds helps to with stand the P deficiency in soil, and can enhance N 2 -fixation and nodulation of legume crop (Grandi et al, 1999).…”
Section: Introductionmentioning
confidence: 99%